Integrating Life Cycle Energy into the Design of Façade Refurbishment for a Post-War Residential Building in The Netherlands - Paressa Loussos; Thaleia Konstantinou; Andy van den Dobbelsteen; Regina Bokel (Buildings, 2015)
The existing building stock has been in the focus of European Union policies for energy savings. Nevertheless, energy certification schemes refer mostly to operational energy and usually do not consider aspects related to the life cycle of the building. To look at the overall energy cost during the lifespan of a building, the energy used to produce and assemble the building materials also needs to be included. This paper develops a design methodology for existing residential buildings that aims at decreasing the life cycle energy use as much as possible. This approach was applied on a case study of an existing post-war residential building in Utrecht, The Netherlands. The main focus of this study is to find a design solution for façade retrofitting that considers both embodied and operational energy. The design approach is based on comparing different strategies for the use of façade materials. This design methodology can be replicated in other projects, as the conclusions and recommendations can also be used for future refurbishment projects for which a low operational energy and materials with a low embodied energy are desired.